Contemplating the Monad Who Saves Us: Maximus the Confessor and John of Damascus on Divine Simplicity. (14th April 2019) - Daley, Brian E.
Abstract: Daley explores divine simplicity according to Maximus the Confessor and John of Damascus, grounding his account in their classical philosophical antecedents. He notes that often we think of the sixth and seventh centuries as devoted to questions about Jesus Christ, not about God per se. Admittedly, the aftermath of the Council of Chalcedon produced ongoing controversy in the East regarding the unity of the two natures of Christ, for example, whether Christ had one operation or two. Maximus, a follower of Patriarch Sophronius of Jerusalem, became embroiled in controversy through his firm rejection of the effort by Emperor Heraclius and Patriarch Sergius of Constantinople to unite the churches in the East by holding solely to a single activity and a single will in Christ. Maximus's position won out at the Third Council of Constantinople (680‐1). Daley draws attention here, however, to the relationship of these Christological debates to the understanding of God, and especially what it means to speak of the "divine nature" and the "divine will." This topic required of Christian thinkers not merely philosophical reflection but also Trinitarian reflection. Daley's point is that it well behooves us to look closely into what Maximus and John of Damascus have to say about divine simplicity, in light of the more central controversies in which these Church Fathers were engaged.